Analysis of adnexal masses requiring reoperation following hysterectomy - J., Karthiga Prabhu; Sundaram, Ramya; V., Valli; M., Muthulakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Generally, we would like to preserve ovaries during hysterectomy for benign conditions. Many of them come back with ovarian cysts and pain abdomen. Recently there were ten cases of residual ovaries requiring surgery during a year period which made us analyze these cases. Methods: This retrospective descriptive analysis was conducted in SRM Medical College Hospital and Research Centre. Data about residual ovaries requiring surgery were retrieved from the medical records department and operation records and analyzed. Results: There were ten cases of residual ovaries from January 2015 to December 2015 requiring surgery. In 70% of patients, residual ovary syndrome occurred within 5 years of hysterectomy. Majority (80%) of them were following abdominal hysterectomy. The most common symptom among these patients was chronic pelvic pain. Pelvic adhesions were present in most of the cases. Follicular cyst and hemorrhagic corpus luteum were the commonest pathological findings in the residual ovaries (50%). There were two cases of endometriotic cyst and a case of secondary malignant ovarian tumor with primary growth from stomach in a 40 year old woman for whom hysterectomy was performed five years ago for adenomyosis. Conclusions: When the ovaries are preserved the woman should be properly counseled and should undergo periodic clinical and ultrasonographic follow-up.